Analisis Ulasan Pelanggan Terhadap Persepsi Resiko Dan Keputusan Pembelian Secara Online - Isalman; Ittaqullah, Nurul; I, Farhan Ramadhani (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim: This study aims to determine the effect of customer reviews on perceived risk, the effect of customer reviews on online purchasing decisions, the effect of perceived risk on online purchasing decisions, and the role of perceived risk in mediating the effect of customer reviews on online purchasing decisions at the Shopee marketplace. Design/Method/Approach: The type of research used is explanatory research, which explores the relationship between research variables by testing hypotheses. This research focuses on marketplace users. The analysis technique uses Structural Equation Modeling (SEM) with PLS 4.0. Research Findings: The results of the analysis show that customer reviews have an effect on perceived risk. Customer reviews influence online purchasing decisions. Perceived risk influences online purchasing decisions. Perceived risk does not mediate the effect of customer reviews on online purchase decisions. Theoretical Contribution/Originality: Previous research has revealed a lot about the various risks that arise in buying and selling online. So this study includes and examines the role of customer reviews as an antecedent variable that can reduce risk perceptions in buying and selling online. Practitionel/Pelicy Implications: These findings can form the basis for marketplace management to consistently develop the review page features for each product and encourage online sellers to respond quickly. Research Limitations: This research does not focus on one type of product. So that future research can re-examine these findings on products that have high product prices and risks.